Big data and knowledge sharing in virtual organizations - Gyamfi, Albert, 1974-; Williams, Idongesit (Engineering Science Reference, 2019)
"This book focuses on the influence of big data analytics, artificial intelligence, as well as, tools, methods, and techniques for knowledge sharing processes in virtual organizations. It also examines new organizational forms which relies largely on networking and collaborations through the use of Internet technologies for knowledge flow"--